Value-Addition Pattern of Consumer Products over Life Stages and Design Assessment Method with Quality Function Deployment - FUJITA, Kikuo; NISHIKAWA, Takeshi (Transactions of the Japan Society of Mechanical Engineers Series C, 2001)
Every kind of consumer products is deployed from market-in stage through growing-up stage to maturated stage by gradually shifting its appealing features from fundamental functions to supplemental value-addition over its life stages. This paper proposes a design assessment method for the product definition of a new product, which is an essential key toward market success of consumer products under the today's rapid and competitive product cycle, based on existing products along with such life stages. Since a series of products over life stages share the underlying design concepts, the contents of their quality-function-deployment tables must be partially shared with each other, while the definition of customer attributes is shifted due to their growth and maturation in market. Based on this observation, an assessment method is organized based on quality function deployment and cost-worth graph to facilitate establishment of product definition. Its validity and promise is ascertained through analyzing design changes across three vacuum cleaners in different life stages.